Analisis Kualitas Ruang Terbuka Hijau Taman Monumen Perjuangan Rakyat Jawa Barat - Tiafahmi Angestiwi; Feny Wahyuniati (Jurnal Kajian Ruang, 2022)
ABSTRACTMonument Perjuangan Park is one of the Green Open Spaces. The location of this park is in the center of Bandung and its strategic position so that it is visited by many people, especially on Sundays. The road around the Monument Perjuangan Park is used as a special location for selling street vendors, but many traders violate the rules by selling inside the park area so that many park facilities are damaged and the management and maintenance of the park is not optimal, affecting the quality of the Monument Perjuangan Park as a green open space. This study aims to analyze the quality of Green Open Space based on aspects of accessibility, activities and facilities. This study used a descriptive analysis of the results of observations, questionnaires and documentation studies. The results of the research from the aspects of accessibility, activities and facilities are not available access for the disabled, the absence of information and directions, the unavailability of facilities to carry out play activities, the lack of conservation and biodiversity as well as some park facilities that are not functioning properly and the conditions are damaged so that the quality of the green Open Space of the Monument Perjuangan Park shows poor quality. The recommendation for the solution to solve the problems found is the planning of the development of Green Open Space assets based on aspects of facilities, activities and accessibility in the Monument Perjuangan Park. Keywords: Green Open Space, quality, accessibility, activities, facilities. ABSTRAKTaman Monumen Perjuangan Rakyat Jawa Barat merupakan salah satu Ruang Terbuka Hijau. Lokasi taman ini berada di pusat kota Bandung dan posisinya yang strategis sehingga banyak dikunjungi masyarakat terutama pada hari Minggu. Jalan di sekitar taman Monumen Perjuangan Rakyat Jawa Barat dijadikan lokasi khusus untuk berjualan pedagang kaki lima, namun banyak pedagang yang melanggar aturan dengan berjualan di dalam area taman sehingga banyak fasilitas taman yang rusak serta pengelolaan dan pemeliharaan taman yang tidak optimal sehingga mempengaruhi kualitas taman Monumen Perjuangan Rakyat Jawa Barat sebagai ruang terbuka hijau. Penelitian ini bertujuan untuk menganalisis kualitas Ruang Terbuka Hijau berdasarkan aspek aksesibilitas, aktivitas dan fasilitas. Penelitian ini menggunakan analisis deskriptif dari hasil observasi, kuesioner dan studi dokumentasi. Hasil penelitian dari aspek aksesibilitas, aktivitas dan fasilitas yaitu tidak tersedia akses untuk difabel, tidak adanya informasi dan petunjuk arah, tidak tersedianya fasilitas untuk melakukan aktivitas bermain, kurangnya konservasi dan keanakaragaman hayati serta beberapa fasilitas taman yang tidak berfungsi dengan baik dan kondisi yang rusak sehingga kualitas Ruang Terbuka hijau taman Monumen perjuangan Rakyat menunjukan kualitas yang tidak baik. Rekomendasi solusi untuk menyelesaikan permasalahan yang ditemukan adalah perencanaan pengembangan aset Ruang Terbuka Hijau berdasarkan aspek fasilitas, aktivitas dan aksesibilitas di taman Monumen Perjuangan Rakyat Jawa Barat.Kata Kunci : Ruang Terbuka Hijau, kualitas, aksesibilitas, aktivitas, fasilitas.